Recent Advances in Dual‐Functional Devices Integrating Solar Cells and Supercapacitors. Issue 3 (6th March 2017) - Sun, Yinglun; Yan, Xingbin
Abstract : Although solar cell technology is an effective way to realize the utilization of solar energy, the output power of solar cells cannot be continuous and stable, due to the intermittent nature of the sunlight. Therefore, proper energy storage devices are generally required to store the generated energy of solar cells. Photo‐supercapacitor is a new energy device that combines the photoelectric conversion function of a solar cell with the energy storage capability of a supercapacitor. This dual‐functionality is the main reason why photo‐supercapacitors are receiving more and more interest for their potential applications in future portable and wearable devices. This review presents the development history and the representative research progress of various photo‐supercapacitors, as well as the problems and challenges that still need to be addressed for the construction of better photo‐supercapacitors. Finally, suggestions for future research directions and opportunities in this fascinating field are given. Abstract : In this review, the development history and representative research progress of different kinds of photo‐supercapacitors are introduced, followed by pointing out the problems and challenges that still need to be addressed for building better photo‐supercapacitors. Finally, some proposals for future research directions and opportunities in this fascinating field are given.